Contribuições ao problema de compensação de atrito em válvulas pneumáticas de controle - Plácido, Uberdan da Silva (2019)
Pneumatic valves can be found in the most diverse industrial parks and are used daily in the most diverse control meshes. However, when exposed to the most diverse climatic factors, they tend to increase the friction between their moving parts. When grip occurs, it is common to cause process variability, reducing mesh performance and increasing process inefficiency. Therefore, reducing the variability in control meshes introduced by the valve friction has been highlighted by improving process productivity and reducing operating costs. Based on the presented needs, the present work proposes to reduce the variability of a process increasing the performance index of the mesh and reducing the amount of movement of opening and closing of the valve. To reach this objective, the effects of several model parameters used in the quantification and the compensation of the friction will be evaluated. Based on this evaluation, the effects on a variable amplitude attrition of the pulses will be analyzed, modulating the amplitude of the pulses in a proportional way to the control loop error. Based on the observed effects, the variable amplitude attrition compensator was parameterized and through simulations, the control mesh performance indices and the amount of opening and closing movement obtained by the different methods were compared. After the comparisons between the methods, it was evidenced through the results that the compensator with variable amplitude, which was inspired by a work of the literature, gathered several positive characteristics of other compensators analyzed, that provided a better index of performance of the control mesh with the least amount of opening and closing of the control valve. Therefore, the method, by reducing the amount of valve movements, will be able to extend the life of the control valve until programming a corrective maintenance.